Underlying data for High-Speed Integrated Visible Light Communication System: Device Constraints and Design Considerations - O'Brien, D (University of Oxford, 2015)
Dataset consists of Excel workbook contain underlying data for graphs in paper and Zemax file containing lens configurations used to create plots of optical system performance